Iron status in breast-fed full-term infants - Arvas, Ahmet; Elgörmüş, Yusuf; Gür, Emel; Alikaşifoğlu, Müjgan; Çelebi, Ahmet (The Turkish Journal of Pediatrics, 2000)
The aim of this study was to evaluate the iron status of full-term babies breast-fed exclusively for four months and the importance of iron supplementation. One hundred sixteen term infants followed up since the newborn period by a well baby clinic were included in the study. Iron deficient and/or anemic infants were excluded from the study at four months. Some of the infants (51) were later given appropriate complementary food besides breast-feeding (Group A) and some (42) were given ferrous sulfate (1 mg/kg/d) (Group B). Blood count and serum iron and ferritin measurements were done at four and six months of age.At the 4th month, iron deficiency was found in 23 (19.8%) infants, 11 of which had iron deficiency anemia. At the 6th month, 23 (45%) infants in Group A were iron deficient and 11 (21.6%) of them had iron deficiency anemia. In Group B, three (7.1%) infants were iron deficient and one (2.4%) of them also had iron deficiency anemia (p < 0.0001).Significant iron deficiency and iron deficiency anemia have been found in four-month-old exclusively breast-fed full-term infants. It is observed that complementary food alone is insufficient; there is need for iron supplementation.
Keywords: iron deficiency anemia; exclusive breast feeding; full-term infant; iron supplementation